Low thermal budget, photonic-cured compact TiO2 layers for high-efficiency perovskite solar cells. Issue 24 (7th June 2016) - Das, Sanjib; Gu, Gong; Joshi, Pooran C.; Yang, Bin; Aytug, Tolga; Rouleau, Christopher M.; Geohegan, David B.; Xiao, Kai
Abstract : High-efficiency perovskite solar cells were fabricated using low thermal budget photonic-cured compact TiO2 as the electron transport layer. The best device on glass substrate exhibited an efficiency of 15% with average efficiency of 12.7%, comparable to the devices with furnace-annealed TiO2 . Flexible devices were as efficient as 11.2%. Abstract : Rapid advances in organometallic trihalide perovskite solar cells (PSCs) have positioned them to be one of the leading next generation photovoltaic technologies. However, most of the high-performance PSCs, particularly those using compact TiO2 as an electron transport layer, require a high-temperature sintering step, which is not compatible with flexible polymer-based substrates. Considering the materials of interest for PSCs and corresponding device configurations, it is technologically imperative to fabricate high-efficiency cells at low thermal budget so that they can be realized on low-temperature plastic substrates. We report on a new photonic curing technique that produces crystalline anatase-phase TiO2 films on indium tin oxide-coated glass and flexible polyethylene terephthalate (PET) substrates. The planar PSCs, using photonic-cured TiO2 films, exhibit PCEs as high as 15.0% and 11.2% on glass and flexible PET substrates, respectively, comparable to the device performance of PSCs incorporating furnace annealed TiO2 films.